2022
DOI: 10.1021/acsaem.1c04028
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Light Harvesting in Thick Perovskite Solar Cells Processed on Industry-Applicable Random Pyramidal Textures

Abstract: Light management is key to high-performance solar cells, particularly to monolithic perovskite/Si tandem solar cells and in real field applications. Random pyramidal textures of commercial Si solar cells (height ∼2–5 μm) allow for efficient light harvesting; however, solution processing of conventional perovskite thin films (thickness ∼0.5 μm) over these large textures exhibits bad coverage, resulting in shunting paths. In response to this challenge, we present high-efficiency perovskite solar cells (PSCs) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
(196 reference statements)
0
14
0
Order By: Relevance
“…Various studies have already demonstrated the feasibility of such high thicknesses in perovskite absorbers while maintaining high charge carrier mobility. [24,[51][52][53] Finally, replacing the front MgF 2 antireflection coating with micro-textures will improve the PCE by 0.73% (see Figure 4c). Micro-textures increase the probability of light in-coupling by allowing multiple reflections at the textured surface and increase the optical pth length through the absorber.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have already demonstrated the feasibility of such high thicknesses in perovskite absorbers while maintaining high charge carrier mobility. [24,[51][52][53] Finally, replacing the front MgF 2 antireflection coating with micro-textures will improve the PCE by 0.73% (see Figure 4c). Micro-textures increase the probability of light in-coupling by allowing multiple reflections at the textured surface and increase the optical pth length through the absorber.…”
Section: Discussionmentioning
confidence: 99%
“…The substrates were heated up to 300 °C for 75 min in the vacuum chamber before deposition and this temperature was maintained during the whole deposition process, the deposition parameters can be found in ref. [80] The average sheet resistance of the ITO films was ≈14 Ω cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…[90,102] We find that the 1.6 m perovskite precursor solution (which is essential to provide full surface coverage over the micrometer-sized pyramidal textures as discussed in the next section) results in a high volume fraction of PbI 2 when processed over a planar Si substrates employing 10% excess PbI 2 (see XRD spectra in Figure 3a). [80,112] Interestingly, the PbI 2 diffraction peak intensity is strongly decreased once the perovskite thin film is processed over the textured surface compared to the planar reference. We emphasize that we used the same perovskite precursor solution and the same processing parameters for both the textured and planar Si substrates.…”
Section: Effect Of Precursor Stoichiometry On Voltage Lossesmentioning
confidence: 99%
See 2 more Smart Citations